The Principle of Good Faith in the Sale and Purchase Agreement of Rights Made Before a Notary - I Gusti Ngurah Muliarta (Community Service Journal of Law, 2022)
In an agreement, good faith plays an important role, because with the good faith shown by the parties in making an agreement, the parties will feel protected. In the land sale and purchase agreement made before a notary, the seller has an obligation to provide honest information about the condition of the land to be sold and nothing is covered up. Likewise, the buyer must check the location of the land to be purchased carefully, to find out in advance whether the purchased land can be built or not. This study will examine and analyze the principle of good faith in legal provisions, especially in contract law. Good faith is still often a matter of debate, because there are still many parties who enter into an agreement who are dragged into legal problems in court, including those with good intentions. Good faith must exist from the pre-contract where the parties start negotiating until reaching an agreement until the contract implementation phase. This research will examine the problems: Is the good faith in the sale and purchase agreement of land rights made before a Notary obliged to accommodate the principles of rationality and propriety? This research uses normative legal research, namely by using primary legal materials and secondary legal materials, then the approach used is the approach to legislation, concepts and philosophy, legal history and comparative law approach. The findings in this study are good faith in a sale and purchase agreement of land rights based on the contents of the agreement containing the principles of rationality and propriety. The context of good faith in Article 1338 paragraph (3) of the Civil Code is based on rationality and propriety. The standard used in assessing good faith in the implementation of the contract is an objective standard. With this standard, the behavior of the parties in carrying out the contract and the assessment of the contents of the contract are based on the principles of rationality and propriety. Good faith has a very important role in making an agreement, including in the sale and purchase agreement of land rights made before a notary in order to minimize the possibility of fraudulent practices in the sale and purchase transaction.